THE IMPACT OF E-CIGARETTE USE ON LUNG FUNCTION AND RESPIRATORY HEALTH - Mohammed Jawad Alabdulwahhab, Akeel Abdullah Al Wahaimed, Aqeel Ali Alnofaily, Ayesh Eid Albogami, Wardah Matuq Alrashed, Ali Ibrahim Ali Alkadi, Ali Saleh Hassan Aljubran, Atheer Mansoor Alawad,; Mohammad Jahaz Alanazi, Loaey Nasser Alalawi, Ayat Mohammed Sukairi, Omniah Abdulkarim Alzaher, Maitham Faisal Alghulam, Amal Abdullah Al Abbas, Abduljallil Ali Alabbad, (Chelonian Research Foundation, 2022)
Given the increasing popularity of e-cigarettes (ECs), it is crucial to gather research about their impact on health in order to guide healthcare practices and policy decisions. Regulators and health experts have expressed worries that the fine particles produced by electronic cigarettes (ECs) may include various substances that might be harmful to respiratory health. We provide a thorough evaluation of published data on the respiratory system, including the impact of electronic cigarettes (ECs) on preclinical models, clinical trials involving individuals who transitioned from tobacco cigarettes to ECs, and demographic surveys. We evaluate the research based on the rigor of their methodology and the precision of their interpretation. It is crucial to prioritize the rapid development of strong and practical methodological suggestions in order to accurately evaluate the effects of EC usage on human health and solve frequent errors. The results of this analysis suggest that electronic cigarettes, when used normally, provide much less respiratory hazards compared to traditional tobacco cigarettes. Users of electronic cigarettes (ECs) and those who smoke and are contemplating using ECs have the entitlement to receive accurate information about the comparative hazards associated with EC usage. They should also be warned that the conclusions drawn from research reported in the media may not always be trustworthy. Increasing research substantiates the comparative safety of EC emission aerosols for the respiratory system in comparison to tobacco smoke. Keywords: E-cigarette, respiratory health, nicotine, smoking, reviews.